2005
DOI: 10.1038/sj.bjc.6602848
|View full text |Cite
|
Sign up to set email alerts
|

Spread of human cancer cells occurs with probabilities indicative of a nongenetic mechanism

Abstract: There has been much uncertainty as to whether metastasis requires mutation at the time of spread. Here, we use clinical data to calculate the probability of the spread of melanoma and breast cancer cells. These calculations reveal that the probability of the spread of cancer cells is relatively high for small tumours (B1 event of spread for every 500 cells for melanomas of 0.1 mm) and declines as tumours increase in size (B1 event of spread for every 10 8 cells for melanomas of 12 mm). The probability of sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
1
36
0
1
Order By: Relevance
“…We have observed that, when information is available only on tumor size, a simple expression, the SizeOnly equation, accurately captures the relation between primary tumor size and lethality, as observed from our data on patients with breast carcinoma, renal cell carcinoma, and melanoma [1][2][3][4] (for the SizeOnly equation, see Equation 1 from the accompanying article 4 ). We also have observed that the relation between tumor size and the risk of cancer in the lymph nodes is captured well by a variant of the SizeOnly equation, the NodalSizeOnly equation (see Equation 1n in the accompanying article 4 ), as indicated by data from patients with breast carcinoma and patients with melanoma.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…We have observed that, when information is available only on tumor size, a simple expression, the SizeOnly equation, accurately captures the relation between primary tumor size and lethality, as observed from our data on patients with breast carcinoma, renal cell carcinoma, and melanoma [1][2][3][4] (for the SizeOnly equation, see Equation 1 from the accompanying article 4 ). We also have observed that the relation between tumor size and the risk of cancer in the lymph nodes is captured well by a variant of the SizeOnly equation, the NodalSizeOnly equation (see Equation 1n in the accompanying article 4 ), as indicated by data from patients with breast carcinoma and patients with melanoma.…”
mentioning
confidence: 84%
“…Apparently, the probability of an event of lethal spread, per cell, is the same regardless of the site from which the cancer cells originate. It often has been wondered whether mutation at the time of spread is a requirement for metastasis [8][9][10][11][12][13][14][15][16][17] ; however, following the reasoning outlined previously, 3 the values for the probabilities of metastatic spread of breast carcinoma, renal cell carcinoma, and melanoma cells presented here are difficult to reconcile with such genetic change: First, the value of the probability of lethal spread for the smallest melanomas (0.1 mm), at approximately 1 event of spread for every 500 cells, is many orders of magnitude greater than that expected for a genetic change. Second, the probability of metastatic spread per cell from the primary site declines as the tumor increases in size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations